Hypoxic Characteristic Genes Predict Response to Immunotherapy for Urothelial Carcinoma - Hong, Shuo; Zhang, Yueming; Cao, Manming; Lin, Anqi; Yang, Qi; Zhang, Jian; Luo, Peng; Guo, Linlang (Frontiers in Cell and Developmental Biology, 2021)
Objective: Immune checkpoint inhibitor (ICI) resistance is a major reason for the poor efficacy of patients treated with ICI in metastatic urothelial cancer(mUC). Hypoxia can trigger tumor malignant biological behavior and immunosuppressive process. Therefore, it is necessary to determine the relationship between the degree of hypoxia infiltration and survival prognosis in metastatic urothelial carcinoma, and explore its possible mechanism. Methods: We collected transcriptome and clinical data of 326 mUC patients treated with ICI, randomly divided the data into training set and test set, and downloaded hypoxia-related gene sets from the molecular signatures database (MSigDB). A univariate Cox regression was carried out in the training set to screen hypoxia genes related to prognosis, and then a multivariate Cox regression was used to construct a prognostic model. We also collected two melanoma cohorts treated with ICI to verify the accuracy of the model. The bladder cancer cohort was downloaded from the Cancer Genome Atlas (TCGA) database together with mUC traing set and test set to explore the mechanism from clinical features, gene mutation, immune infiltration, pathway enrichment and drug sensitivity. Results: According to a 4-gene hypoxia risk prognostic model we have conducted, we found that patients with high hypoxia risk score had shorter OS. The area under the ROC curve of training set and test set of the model is 0.71 and 0.59 respectively, which is better than the survival prediction of mUC patients with clinical characteristics. Mutation results show that most of RB1, TP53, TSC1 and KDM6A have deletion mutations in hypoxia environment. Immune cell infiltration analysis showed that the degree of infiltration of T cells, B cells, Treg cells and macrophages was higher than that of low infiltration in hypoxic environment. Pathway function enrichment analysis showed that hypoxia environment activated inflammatory pathways, glucose metabolism pathways and immune-related pathways, which jointly acted on biological processes. Conclusion: A 4-gene score model was constructed to evaluate the degree of hypoxia and survival prognosis of patients treated with ICI and showed a promising clinical prediction value in metastatic urothelial cancer. Futhermore, the possible mechanism of immunosuppression caused by hypoxia environment is discussed.